Sustainable Development of Digital TV Business Operators: A Case Study of National Business Service Channel Group - Sukijjakorn, Thanasak (Arts of Management Journal, 2020)
The objectives of this research were 1) to analyze the factors of good corporate governance that influence on business sustainability; 2) to analyze the factors of media ethics standards that influence on business sustainability; 3) to analyze the factors of audience satisfaction that influence on Business sustainability; and 4) to give suggestions on the development of Digital TV operators. The study was a mixed methods research. 1) Quantitative research uses a research framework in good corporate governance concepts, Audience satisfaction, Media Ethics Standards, Business sustainability. Research area in 5 regions in Thailand (north, central, south, east, northeast). A sample of 500 cases were drawn from digital TV viewers, using simple random sampling method. Research tools used in this research were questionnaires, and 2) Qualitative research using purposive sampling methods and in-depth interview with the Digital TV business operator, Digital TV regulator (NBTC.), Digital TV viewers. Research tools used in the research were Semi Structure Interview. The results of the study were as follows: 1. The research in objective 1: Good corporate governance had a positive influence on business sustainability. The research in objective 2: Media ethics standards had a positive and indirect influence on business sustainability. The research in objective 3: Audience satisfaction had a positive influence on business sustainability. This research Digital TV operators should pay attention to good corporate governance, audience satisfaction and media ethics standards. In order to be effective and able to develop a Digital TV business sustainably